Proposta de protocolo para o desenvolvimento e avaliação de órtese customizada de punho-mão utilizando tecnologias 3D - Schmitz, Cristiane (2019)
Cerebral Palsy (CP) is a group of permanent disorders related to movements and postures that affects the infant brain. Such disorders can alter children communication skills, movement coordination, strength, behavior and sensation function. CP is the most common type of disability in childhood, and affects more than 100 million children. The most common alterations of CP are the muscle spasticity. On the upper limb, spasticity presented as a flexion pattern, increase the difficulties regarding their hand abilities. So, to overcome this issue, functional orthoses are being employed as therapeutic intervention and can allow children with CP to have an opportunity to better use their hands and improve hand abilities as well. This medical advice could be customized, and reach high level by using three-dimensional (3D) technologies. 3D technologies can provide the generation of high-quality orthopedic products, created unique designs and quality. As a result, orthoses develop by this technology; increase the patient satisfaction, further provided higher adhesion and usability. Therefore, the purpose of this research is to propose production protocol for develop a customized functional wristhand orthosis using 3D technology. For that, it was used high-level 3D scanning to acquire the wrist-hand anatomy, a free software for 3D modelling and a low-cost 3D printer for manufacturing the orthosis. In addition, we evaluated the functionality of the proposed wristhand orthosis, using unilateral hand abilities the Jebsen-Taylor test of hand Function (JTTHF). The protocol suggested by this research was able to develop a functional orthosis using 3D technology. The functional orthosis developed on this research was able not only to improve functional hand skills, but also to provide comfort, better fitting within aesthetic design required by the patient. On this research was observed improvements on hand abilities for writing (13s), lifting small objects (0.9 s) and simulated feeding (69.3 s) while wearing the orthosis by the affected hand.